Perception of nurses on the adhesion of partners of pregnant women with syphilis to the treatment - Mayanne Santana Nóbrega de Figueiredo; Edilma Gomes Rocha Cavalcante; Célida Juliana de Oliveira; Maria de Fátima Vasques Monteiro; Glauberto da Silva Quirino; Dayanne Rakelly de Oliveira (Rev Rene)
Objective: to investigate the perception of nurses of the Family Health Strategy on the factors that influence adhesion totreatment of sexual partners of pregnant women with syphilis. Methods: it is a qualitative research, made with 10 nurses.To collect data, a semi-structured interview was used. The data were submitted to thematic analysis. Results: the followingcategories were identified: the approach of the nurses to partners of pregnant women with syphilis; barriers that influenceon the adhesion to the treatment; strategies and actions of adhesion of the partners in the treatment; perception of the nurseconcerning the responsibility of assistance and effectiveness of the treatment. Conclusion: it was identified that nurses havea wide perception of aspects relating to adhesion to the treatment, but need better scientific and practical basis to performeffectively activities on the management of sexual partners with syphilis.